1998
DOI: 10.1086/305707
|View full text |Cite
|
Sign up to set email alerts
|

Topological Formation of Small Scales in Magnetohydrodynamics: A Fast Dissipation Mechanism

Abstract: The dissipation of Alfve n wave packets propagating in an inhomogeneous three-dimensional magnetic Ðeld is numerically studied in the Wentzel-Kramers-Brillouin (WKB) approximation. The dissipation rate is found to scale proportionally to the logarithm of viscosity and/or resistivity, i.e., much faster than the scaling found for two-dimensional conÐgurations (phase mixing, resonance absorption). This phenomenon is related to the exponential separation of neighboring rays ; estimations of the corresponding rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 22 publications
3
37
0
Order By: Relevance
“…2D and 3D structuring can dramatically affect properties of MHD waves. In particular, as it was shown in the incompressible regime by Similon & Sudan (1989) and confirmed in numerical experiments performed by Petkaki et al (1998) and Malara et al (2000), the structuring dramatically increases the efficiency of wave dissipation. However, in those studies, the compressible effects were not taken into account.…”
Section: Introductionsupporting
confidence: 59%
“…2D and 3D structuring can dramatically affect properties of MHD waves. In particular, as it was shown in the incompressible regime by Similon & Sudan (1989) and confirmed in numerical experiments performed by Petkaki et al (1998) and Malara et al (2000), the structuring dramatically increases the efficiency of wave dissipation. However, in those studies, the compressible effects were not taken into account.…”
Section: Introductionsupporting
confidence: 59%
“…Another assumption is that the wavelength λ of the perturbation stays much smaller than the scale length L 0 of the equilibrium structure (λ L 0 ). During the evolution, the wavelength λ tends to decrease in time (Petkaki et al 1998). Thus, the above condition is always fulfilled, provided that it is satisfied at the initial time.…”
Section: Alfvén Waves In An Inhomogeneous Magnetic Fieldmentioning
confidence: 90%
“…In this paper we have characterized the property of small-scale generation in small-amplitude Alfvénic perturbations propagating in an inhomogeneous equilibrium magnetic structure, within the framework of a WKB approximation (Petkaki et al 1998;Malara et al 2003). The growth of the wavevector k in the perturbation is intimately related to the property that nearby field lines of the c (0) A field move apart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have shown that the creation of a dissipative scale can be made exponentially fast (dk/dt ∝ const.·k), with the associated time scale being proportional to ln S S 1/3 S (Similon & Sudan 1989;Petkaki et al 1998;Malara et al 2007). The latter improved efficiency of the dissipation results by essentially considering a more complex magnetic geometry, with the property of local exponential separation or divergence of neighboring magnetic field lines.…”
Section: Introductionmentioning
confidence: 99%